2023
DOI: 10.1039/d2ee03936b
|View full text |Cite
|
Sign up to set email alerts
|

Methanol upgrading coupled with hydrogen product at large current density promoted by strong interfacial interactions

Abstract: Anodic organic upgrading offers a promising strategy to produce value-added chemicals and facilitate coupled hydrogen production but is still challenging for long-term stability and high activity of electrocatalysts at large...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 51 publications
1
65
0
Order By: Relevance
“…The above results demonstrate that CoNi-DSA/NG possesses higher catalytic activity than Co-SA/NG and Ni-SA/NG, which may be attributed to the catalytic synergism between Co and Ni atoms. 47,48 Moreover, to explore the catalytic kinetics, the Tafel slopes of catalysts were plotted by linearly fitting the polarization curves. The Tafel slope of CoNi-DSA/NG is 81 mV dec À1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above results demonstrate that CoNi-DSA/NG possesses higher catalytic activity than Co-SA/NG and Ni-SA/NG, which may be attributed to the catalytic synergism between Co and Ni atoms. 47,48 Moreover, to explore the catalytic kinetics, the Tafel slopes of catalysts were plotted by linearly fitting the polarization curves. The Tafel slope of CoNi-DSA/NG is 81 mV dec À1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The above results demonstrate that CoNi-DSA/NG possesses higher catalytic activity than Co-SA/NG and Ni-SA/NG, which may be attributed to the catalytic synergism between Co and Ni atoms. [47,48] Moreover, to explore the The Tafel slope of CoNi-DSA/NG is 81 mV•dec -1 (Figure 5c), which is lower than those of Co-SA/NG (125 mV•dec -1 ) and Ni-SA/NG (143 mV•dec -1 ). The result indicates that CoNi-DSA/NG possesses a faster OER rate in alkaline solutions [49] .…”
Section: Energy Advances Accepted Manuscriptmentioning
confidence: 97%
“…19−21 Among the above-mentioned electrocatalysts, nickel-based oxides exhibited high OER activity, especially in alkaline environments. 22,23 The mixture of 3d transition metal and 4d transition metal oxides displayed notable electrocatalytic activity. 9,24 In this point, tungstate-based materials have been brought into consideration for total water splitting.…”
Section: ■ Introductionmentioning
confidence: 99%
“…During water electrolysis, oxygen evolution reaction (OER) which occurs at the anode is more sluggish kinetic due to four-electron transfer which leads to increase in the activation energy barrier . Till date, transition metal oxides such as ruthenium and iridium (RuO 2 and IrO 2 ) are regarded as effective noble electrocatalysts for the OER reaction in alkaline condition. , However, their scarcity and high cost are unsuitable for large-scale usage. Therefore, researchers have to design a low cost, earth abundant transition metal-based catalyst possessing a low overpotential and high stability toward hydrogen generation in large scale as compared to noble metals. Transition metal hydroxides, oxides, phosphides, ,, and chalcogenide-based materials have been regarded as efficient electrocatalysts toward water splitting at various pH conditions. , However, the obtained hydroxide or oxide during OER will act as the electrochemically active site of numerous catalysts which are mentioned above. Among the above-mentioned electrocatalysts, nickel-based oxides exhibited high OER activity, especially in alkaline environments. , The mixture of 3d transition metal and 4d transition metal oxides displayed notable electrocatalytic activity. , In this point, tungstate-based materials have been brought into consideration for total water splitting. , Among several catalysts, tungstate and molybdate-based materials have attracted much attention among the researchers, and addition of iron over 4d transition metal oxides ensured enhancement in an electrocatalytic performance . Also, heteroatom doping is a most effective route to create deformation of atoms by lattice strain, which greatly enhances the intrinsic activity of a catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…The stability considerations in most of the literature are limited to the stability test range of ∼10 to ∼100 h at a current density of 10 mA cm –2 . Notably, a scarcity of catalysts meets the stringent industrial criteria that OWS processes have to be catalytically reacted at hundreds of current densities (≥500 mA cm –2 ) and ultralow overpotentials ≤300 mV for long periods of time, which hinders the industrial development of electrocatalysts. , In the process of high current water splitting, a large number of bubbles will be formed rapidly under high current density, and these bubbles have strong adhesion, and the catalyst may also fall off when the bubbles leave, and the number of exposed active sites is reduced, causing low electrocatalytic activity and poor stability. , Previous studies have demonstrated that the open nanoarray framework has the ability to release the bubbles, and the strong contact with the conductive substrate can effectively prevent the catalyst from peeling off, thus ensuring its long-term stability. The creation of a heterojunction structure on the surface of a nanoarray electrocatalyst allows for an increase in the intrinsic activity of the catalyst through electronic interactions at the contact interface of the two nonhomogeneous structural active components, thus promoting the activity of the material and modulating the adsorption behavior of the reaction intermediates. Therefore, to further improve the catalytic performance of the OWS, nanoarray structure design and heterojunction structure construction are needed to optimize the electronic structure and improve hydrogen evolution reaction (HER) and OER activities.…”
mentioning
confidence: 99%